Growing up Untouchable in India: A Dalit Autobiography - Moon, Vasant; Omvedt, Gail; Zelliot, Eleanor (Rowman & Littlefield Publishers, 2002)
In this English translation, Moon's story is usefully framed by apparatus necessary to bring its message to even those taking their first look at South Asian culture...The result is an easy to digest short-course on what it means to be a Dalit, in the words of one notable Dalit.'-Journal of Asian Studies